Use of expert consensus to develop a shared list of procedures with potential for aerosol generation during the coronavirus disease 2019 (COVID-19) pandemic - Dana E. Pepe; Preeti Mehrotra; Lou Ann Bruno-Murtha; Robert Colgrove; Shira Doron; Robert Duncan; Richard Ellison; Sarah Haessler; David C. Hooper; Michael Klompas; Cassandra M. Pierre; Thomas J. Sandora; et al. (Cambridge University Press, 2023)
The coronavirus disease 2019 (COVID-19) pandemic highlighted the lack of agreement regarding the definition of aerosol-generating procedures and potential risk to healthcare personnel. We convened a group of Massachusetts healthcare epidemiologists to develop consensus through expert opinion in an area where broader guidance was lacking at the time.